2012
DOI: 10.1002/ccd.24415
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular embolization of a third jejunal artery aneurysm: Isolation technique using the amplatzer vascular plug 4

Abstract: Aneurysm of the jejunal artery (JA) is very uncommon with few specific symptoms, but can be a lethal entity. When at risk to rupture, it must be treated expeditiously to avoid mortality. We report a case of a 76-year-old male patient that underwent contrast-enhanced multi-detector computed tomography (MDCT) which incidentally reveals a 12 mm saccular aneurysm of the third JA at the bifurcation of the first arcade. Patient underwent successful endovascular embolization using the isolation technique with the Amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 12 publications
2
18
0
1
Order By: Relevance
“…Endovascular isolation involves the embolization of vessels both distally and proximally to the aneurysm, leading to occlusion . In our case, this technique was performed because of the huge aneurysm size, and there were no remarkable branches from the aneurysm.…”
Section: Discussionmentioning
confidence: 98%
“…Endovascular isolation involves the embolization of vessels both distally and proximally to the aneurysm, leading to occlusion . In our case, this technique was performed because of the huge aneurysm size, and there were no remarkable branches from the aneurysm.…”
Section: Discussionmentioning
confidence: 98%
“…A range of different techniques are available to stop the hemorrhage once the bleeding source has been identified. When the target vessel is terminal in location, its proximal embolization is usually enough to stop the bleeding; on the other hand, if collaterals are A B C D E F present, both the inflow and outflow vessels have to be embolized (the so-called "sandwich" technique) in order to avoid re-bleeding ( Figure 1) (70). Vascular occlusion can be obtained exploiting a wind range of materials, with the choice made primarily according to the desired type of vascular occlusion (transient or permanent).…”
Section: Techniques and Scenariosmentioning
confidence: 99%
“…This eliminates the need for catheter exchanges and allows delivery and deployment of the device in smaller, remote, and extremely tortuous vessels as demonstrated in our patient. While the AVP-IV has been used for occlusion of arteriovenous fistulas after saphenous vein harvesting, coronary artery fistulas and aortopulmonary collaterals, intercostal arteries from left internal mammary bypass grafts, and for a variety of peripheral indications,[11121314] to the best of our knowledge, this is the first case of embolization of three PAVMs with AVP-IV devices. Similar to other reports we found that only a single AVP-IV device was adequate to achieve complete and rapid occlusion of the vessel.…”
Section: Discussionmentioning
confidence: 99%